Dysregulation of Amyloid Precursor Protein Impairs Adipose Tissue Mitochondrial Function and Promotes Obesity - An, Yu A. (Nat Metab, 2019)
Mitochondrial function in white adipose tissue (WAT) is an important yet understudied aspect in adipocyte biology. Here, we report a role for amyloid precursor protein (APP) in compromising WAT mitochondrial function through a high-fat diet (HFD)-induced, unconventional mis-localization to mitochondria that further promotes obesity. In humans and mice, obese conditions significantly induce APP production in WAT and its enrichment in mitochondria. Mechanistically, a HFD-induced dysregulation of signal recognition particle subunit 54c is responsible for the mis-targeting of APP to adipocyte mitochondria. Mis-localized APP blocks the protein import machinery, leading to mitochondrial dysfunction in WAT. Adipocyte-specific and mitochondria-targeted APP overexpressing mice display increased body mass and reduced insulin sensitivity, along with dysfunctional WAT due to a dramatic hypertrophic program in adipocytes. Elimination of adipocyte APP rescues HFD-impaired mitochondrial function with significant protection from weight gain and systemic metabolic deficiency. Our data highlights an important role of APP in modulating WAT mitochondrial function and obesity-associated metabolic dysfunction.